URGENSI PERATURAN DAERAH DALAM PENYELENGGARAAN PENANGGULANGAN BENCANA - Massi, Randy Atma R. (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
The formation of laws and regulations, must determine the rules for the formation of invitation regulations or statutory regulations (gesetzgebungslehre), which are approved by the juridists. Every legal product must have a legal juridical basis (juridische gelding). This juridical basis is very important in making special laws and regulations. In addition, the relevant Regional Regulation will also provide legal umbrella / legal certainty for stakeholders (executive, legislative, vertical institutions, community, and other parties) who are involved directly or indirectly in the involvement. In order to provide protection to the people in the regions from natural disasters, non-natural disasters and social disasters.